PLANIFICACIÓN DEL DESARROLLO EN ARGENTINA. UNA AGENDA DE AVANCES Y DESAFÍOS ABIERTOS (2003-2015) - Ariel O. García (Boletín Geográfico)
This paper attempts to analyze the conceptual trends that have been influencing national public policies related to regional and sectoral planning directed from the driving state to the period 2003-2015. In particular, a study assessing the conceptual planning from a neo-structuralist perspective arises. To this end, national policies are systematized with regional and sectoral orientation. Since the mid-2000s, the pace of recovery of state regulation, the regional issue has emerged again as an issue in the agenda of public policies. In the period 2003-2015 it has operated a crystallization of new impetus to the development of regional economies. It has tried variety of instruments that can partially sustain the legacy of planning but have also incorporated new aspects (e.g. promotion of social economy, self-management and family farm, guidance and impetus to the demand for grassroots and media, etc.). In this historical context, questions have again become relevant to public management what, who, how, how much and where it occurs, and which means of distribution and accumulation are. Overall, regional and sectoral development policies have been characterized by dispersion and overlapping entities understood in the art. Identified between middle of the first and second decade of the century, they seem to be due to a "settling" of public regulation instruments that have managed persistence (adapted, re-routed) beyond the historical moments that gave rise to them. It has prevailed inertial one, scarcely transformative of power relations inherited from the late twentieth century reformist logic, however situation has allowed the strengthening of the planning functions. Moreover, it is clear that multiple instruments tend to build objects which usually overlap and even interfere. They seem to have arisen by circumstantial situations more product state planning, a situation that disputes the fact whether state inspiration as a whole has been neo-structuralist or more basically oriented to promoting aggregate demand. In any case, Argentina has built its own way a number of instruments of regional and sectoral focus of neo-structuralist inspiration. In this context, public policies outlined here would tend to boost demand centrally, without the possibility of transforming the unbalanced production structure inherited from the previous but attentive to your temporal becoming decades.